Proposed Draft of Key Risk Indicators in the Implementation of ERM in Press Companies in Indonesia (Case Study on PT PPI) - Dewi Mardiani; Ancella Anitawati Hermawan (Green Publisher Indonesia, 2025)
This research aims to develop a framework and matrix for Key Risk Indicators (KRI) to address significant risks, thereby supporting the implementation of Enterprise Risk Management (ERM) within press organizations. Employing a qualitative methodology, the study adopts a case study approach focusing on the primary business process of PT PPI, specifically its news production activities. The investigation is motivated by challenges confronting the press industry amidst rapid digital technological advancements, which have reshaped public consumption patterns of mass media. PT PPI, a newly established press company leveraging cutting-edge technology, currently lacks adequate tools for risk monitoring. To address this gap, the study applies a Risk Control Self-Assessment (RCSA) framework to identify and analyze the risks faced by the organization. Among the 82 risks identified, 26 were deemed critical, with 10 exhibiting a substantial impact on the company. These risks were categorized into four main groups: operational, legal, reputational, and technological risks. The study culminated in the design of 24 Key Risk Indicators, providing a structured and systematic approach to enhancing risk management practices.